Exchange Rate and Price Dynamics at the Zero Lower Bound - Daniel Kaufmann; Gregor Bäurle (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
In this paper, we analyse nominal exchange rate and price dynamics after risk shocks with short-term interest rates constrained by the zero lower bound (ZLB). We show with a stylized theoretical model that temporary risk shocks may lead to permanent shifts of the exchange rate and the price level if a central bank anchors long-run inflation expectations. In line with this theoretical prediction, we find empirical evidence for Switzerland, that the responses of the exchange rate and the price level to a temporary risk shock are permanent. Our theoretical discussion shows that adopting a credible long-run price level target rather than a long-run inflation target avoids these permanent shifts of the exchange rate and the price level.
Keywords: C32; E31; E52; 330